Association between serum osmolality and risk of in-hospital mortality in patients with intracerebral hemorrhage - Hu, Zhaosuo; Sha, Quan (Frontiers in Neurology, 2024)
Aim This study aimed to analyze the association between serum osmolality and the risk of in-hospital mortality in intracerebral hemorrhage (ICH) patients. Methods In this retrospective cohort study, data of a total of 1,837 ICH patients aged ≥18 years were extracted from the Medical Information Mart for Intensive Care-IV (MIMIC-IV). Serum osmolality and blood urea nitrogen (BUN)-to-creatinine (Cr) ratio (BCR) were used as the main variables to assess their association with the risk of in-hospital mortality in ICH patients after first intensive care unit (ICU) admission using a univariable Cox model. Univariable and multivariable Cox regression analyses were applied to explore the associations between serum osmolality, BCR, and in-hospital mortality of ICH patients. Hazard ratio (HR) and 95% confidence intervals (CIs) were calculated. Results The median survival duration of all participants was 8.29 (4.61–15.24) days. Serum osmolality of ≥295 mmol/L was correlated with an increased risk of in-hospital mortality in patients with ICH (HR = 1.43, 95%CI: 1.14–1.78). BCR of >20 was not significantly associated with the risk of in-hospital mortality in ICH patients. A subgroup analysis indicated an increased risk of in-hospital mortality among ICH patients who were women, belonged to white or Black race, or had complications with acute kidney injury (AKI). Conclusion High serum osmolality was associated with an increased risk of in-hospital mortality among ICH patients.